Optimum Feeding Rate for the Sub-adult Olive Flounder, Paralichthys olivaceus, Fed Practical Extruded Pellets at Optimum Water Temperature - Shin, Seung-Jun; Shin, Seung-Jun; Bai, Sungchul C.; Bai, Sungchul C.; Lee, Kyeong-Jun; Lee, Kyeong-Jun; Kim, Jeong-Dae; Kim, Jeong-Dae; Kim, Sung-Sam (Indonesian Aquaculture Society (MAI), 2018)
We investigated the effects of feeding rate on the growth, blood components, and histology of the growing olive flounder (Paralichthys olivaceus). We determined the optimum feeding rate (initial fish mean weight = 525.3 ± 7.12 g) at the optimum water temperature. Two replicate groups of fish were fed a commercial diet at rates of 0%, 0.2%, 0.4%, 0.6%, and 0.8% (i.e., to satiation) of body weight (BW) per day. The feeding trial was conducted using a flow-through system, with ten of 1.2-metric-ton aquaria receiving filtered seawater between 20.5 and 24.5°C, for 3 weeks. Weight gain (WG) and specific growth rate (SGR) were significantly greater in fish fed with satiation at 0.8% BW/day compared to fish fed at 0.2% BW/day, and with unfed fish. These parameters were negative, and significantly lower, in the starved fish compared to the fish fed the experimental diet, for all feeding rates. There were no significant differences in WG and SGR among fish fed at 0.2%, 0.4%, and 0.6% BW/day, and among those fed at 0.4%, 0.6% and 0.8% of BW/day. The histological changes in tissues were not significant in the hepatopancreas, kidney, or anterior intestine of fish fed at 0%, 0.4%, and 0.8% of BW/day. Broken-line regression analysis based on weight gain demonstrated that the optimum feeding rate for an olive flounder weighing 525 g was 0.70% BW/day at optimum water temperature.